MORPHO-FUNCTIONAL RELATIONSHIPS IN EXPERIMENTAL ASSOCIATED INFECTION - Сахаров, Сергей Павлович; Молокова, Ольга Александровна; Фролова, Ольга Игоревна; Молокова, Анастасия Сергеевна (Medicine in Kuzbass, 2023)
Relevance. Generalized infections are characterized by a severe course with multiple organ failure. The use of different infection models, the lack of a unified system for assessing organ damage makes it difficult to interpret and extrapolate the results. The purpose of the study – to develop criteria for assessing kidney and liver dysfunction in associated infection modeled by cultivated (CB) and uncultivated bacteria (NCB) of P. aeruginosa and S. aureus. Methods. There were 58 rabbits used in the experiment, divided into III groups. The animals were infected with CB and NCB forms of P. aeruginosa and S. aureus bacteria isolated from the wound contents of patients with thermal trauma. The functional, pathomorphological state of the kidneys and liver was studied, morphometry and statistical analysis were performed. Results. In healthy animals, a statistically significant weak direct linear correlation between biochemical and morphometric parameters characterizing the functioning of the kidneys and liver was revealed. Under the conditions of the SIRS, an increase in the severity of the direct linear correlation to strong and very strong in animals of the IA, IIA and IIB subgroups was noted. There is no correlation in the IB subgroup. A stable statistically significant linear correlation between functional and morphometric indicators reflecting the state of the kidneys and liver indicates the development of hepatoprenal syndrome as a manifestation of the mutual burden syndrome characteristic of generalized infection. Conclusions. Critical periods of violation of correlational relationships are revealed, reflecting the violation of the conjugacy of the functioning of internal organs. When infected with CB, the body’s ability to compensate for structural and functional disorders persists for up to 8 days of the disease. On the 11-12th day, liver and kidney dysfunction develops, maintained and aggravated by the syndrome of mutual aggravation. When infected with NCB, the disease acquires a lightning-fast course. The correlation between biochemical and morphometric parameters is maintained up to 2-5 days. The death of animals on the 8th day of the experiment was caused by a violation of the conjugate functioning of the liver and kidneys, reflecting the early development of multiple organ failure.